HPV infection and pregnancy. Features of diagnostics and management tactics - E. I. Yunusovа; O. V. Danilovа; L. A. Yusupova; G. I. Mavlyutova; Z. Sh. Garaeva (Лечащий Врач, 2021)
The article presents the features of interaction of human papilloma virus (HPV) with the immune system, emphasizes the special relevance of HPV infection during pregnancy and the risk of papillomavirus pathology in children. The data of own research of frequency of occurrence of HPV-associated pathology of extragenital localization in pregnant women with the diagnosis of anogenital warts were presented.